Diogenes kakeroma, a new species of hermit crab (Decapoda: Anomura: Diogenidae) from Amami Islands, Ryukyu Islands, southern Japan - Nagasaka, Tadanosuke; Komai, Tomoyuki (Zootaxa, 2026)
A new species of the diogenid hermit crab genus Diogenes Dana, 1851, D. kakeroma, is described and illustrated based on material from shallow subtidal waters (2–4 m deep) in Amami Islands, Ryukyu Islands, southern Japan. This new species is morphologically similar to D. holthuisi Asakura & Tachikawa, 2010 and D. minimus Komai & Yoshida, 2020, both known from Japanese waters, but is notable for its unarmed antennal acicles, a trait that appears to be unique within the genus. The status of the new species is further validated by phylogenetic analyses using mitochondrial 16S rRNA and COI genes.